Respuesta :

Answer:

[tex]x = -4[/tex]

Step-by-step explanation:

As I was taught in Algebra class, we use the distributive property to solve this, although there are other ways.

[tex]3(x+2)-7 = 5x + 7[/tex]

Step 1: Distribute.

We are going to distribute 3 to [tex]x[/tex] and +2 (positive 2). Which means multiplying 3 to [tex]x[/tex] and 2.

[tex]3(x+2)\\3\cdot x = 3x\\3\cdot 2 = 6\\\\= 3x+6[/tex]

So, therefore, we have [tex]3x+6-7=5x+7[/tex]

Step 2: Combine like terms.

Combining like terms simply means adding, values that are alike. For example, we can only add [tex]x[/tex] and [tex]x[/tex], [tex]y[/tex] and [tex]y[/tex], or a number and another number. Note, we can only combine like terms on one side of the equation, meaning at the end of the equal to sign.

[tex]3x+\bold6\:\:\bold-\bold7=5x+7[/tex]

Here we have +6 and -7, so adding those two would result in -1

So, therefore, we have [tex]3x-1=5x+7[/tex]

Step 3: Solve for [tex]x[/tex]

[tex]3x-1=5x+7[/tex]

  • Subtract both sides by 7

[tex]3x-1=5x+7\\\:\:\:\:-7\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:-7[/tex]

7 - 7 = 0, so it cancels that side out.

-1 + 7 = -8, so we are left with;

[tex]3x-8=5x[/tex]

  • Subtract 3[tex]\bold x[/tex] from both sides

[tex]3x-8=5x\\-3\:\:\:\:\:\:-3x[/tex]

3x - 3x = 0, so it cancels that side out.

5 - 3 = -2, so we are left with;

[tex]-8=2x[/tex]

  • Divide both sides by 2

[tex]\frac{2x}{2}=\frac{-8}{2}[/tex]

2 over 2 cancels out

[tex]\frac{-8}{2} = -4[/tex]

x = -4